Ethylene synthesis in moss protonema - Rohwer, Frauke; Bopp, Martin (Journal of plant physiology, 1985)
Summary: In sterile cultivated protonema of the moss Funaria hygrometrica we found a promotion of ethylene formation by ACC but not by other possible precursors such as 2-ketoglutarate or glutamate. The ACC contents and ethylene formation during development of protonema were correlated. Both ACC contents and ethylene formation were promoted by exogenous IAA. These findings indicate that ethylene production in Funaria protonema follows the normal pathway as in higher plants. The rate of ethylene production lay in the same order of magnitude as in higher plants and depended on the developmental stage of the protonema.
Gesehen am 09.04.2018